Revisiting the gene loss of respiratory requirements for Salmonella Typhimurium and Salmonella Enteritidis in the chicken infection model - Daniel F. M. Monte; Mauro de Mesquita Souza Saraiva; Julia Memrava Cabrera; Adriana Maria de Almeida; Jacqueline Boldrin de Paiva; Lauanda Monteriro Muniz; Tulio Spina de Lima; Oliveiro Caetano de Freitas Neto; Paul A. Barrow; Angelo Berchieri Junior (Brazilian Journal of Microbiology, 2025)

A Transcriptomic Comparative Study of Cranial Vasculature - Jianing Zhang; Jee-Yeon Ryu; Selena-Rae Tirado; Lawrence D. Dickinson; Aviva Abosch; M. Ali Aziz-Sultan; Alan S. Boulos; Daniel L. Barrow; H. Hunt Batjer; Tamar R. Binyamin; Spiros L. Blackburn; Edward F. Chang; et al. (Translational Stroke Research, 2024)

Deliberately introduced dung beetles in A ustralia: 12 years of occurrence and abundance records from 2001 to 2022 - Jacob D. Berson; Penelope B. Edwards; T. James Ridsdill‐Smith; Christopher K. Taylor; Daniel J. Anderson; Nigel R. Andrew; Russell A. Barrow; David A. Cousins; Robert N. Emery; Laura L. Fagan; Rhiannon M. Foster; Lucas G. Harwood; et al. (Ecology, 2024)
Since 1968, the Australian Dung Beetle Project has carried out field releases of 43 deliberately introduced dung beetle species for the biological control of livestock dung and dung‐breeding pests. Of these, 23 species are known to have become established. For most of these species, sufficient time has elapsed for population expansion to fill the extent of their potential geographic range through both natural and human‐assisted dispersal. Consequently, over the last 20 years, extensive efforts have been made to quantify the current distribution of these introduced dung beetles, as well as the seasonal and spatial variation in their activity levels. Much of these data and their associated metadata have remained unpublished, and they have not previously been synthesized into a cohesive dataset. Here, we collate and report data from the three largest dung beetle monitoring projects from 2001 to 2022. Together, these projects encompass data collected from across Australia, and include records for all 23 species of established dung beetles introduced for biocontrol purposes. In total, these data include 22,718 presence records and 213,538 absence records collected during 10,272 sampling events at 546 locations. Most presence records (97%) include abundance data. In total, 1,752,807 dung beetles were identified as part of these data. The distributional occurrence and abundance data can be used to explore questions such as factors influencing dung beetle species distributions, dung beetle biocontrol, and insect‐mediated ecosystem services. These data are provided under a CC‐BY‐NC 4.0 license and users are encouraged to cite this data paper when using the data.

Unravelling the role of anaerobic metabolism (pta-ackA) and virulence (misL and ssa) genes in Salmonella Heidelberg shedding using chicken infection model - Daniel F. M. Monte; Mauro M. S. Saraiva; Julia Memrava Cabrera; Adriana Maria de Almeida; Oliveiro Caetano de Freitas Neto; Paul A. Barrow; Angelo Berchieri Junior (Brazilian Journal of Microbiology, 2024)

Evidence of resident coastal population(s) of false killer whales (Pseudorca crassidens) in northern Australian waters - Carol Palmer; Karen K. Martien; Holly Raudino; Kelly M. Robertson; Alan Withers; Emma Withers; Robert Risk; Dylan Cooper; Ellen D’Cruz; Edmund Jungine; Daniel Barrow; Nick Cuff; et al. (Frontiers in Marine Science, 2023)
To help evaluate the distribution, residency, population size and structuring (and hence conservation status) of the poorly known false killer whale Pseudorca crassidens in northern Australian waters, we undertook studies of sightings, movement patterns based on satellite telemetry, and genetics. Sighting data indicates that false killer whales are regular, year-round inhabitants of coastal areas of northern Australia. Satellite-tagged animals spent extended periods of time in shallow coastal waters, with no tagged animals leaving the continental shelf. The lack of spatial overlap in the areas visited by individuals tagged in the Arafura/Timor Seas compared to those tagged in the Gulf of Carpentaria suggests that there may be more than one population in northern Australia coastal waters. All 14 genetic samples collected across 1600 km of coastline possessed the same newly identified mitochondrial control region haplotype, designated haplotype 45. Notably, haplotype 45 is distinct from all previously published false killer whale haplotypes globally and is most similar to the two haplotypes that typify the endangered main Hawaiian Islands insular false killer whale population. Based on these results and evidence from recent movement records of those tagged, false killer whales in northern Australia are apparently demographically independent from the offshore population(s). Further assessment of the population conservation status is now required.

Regional Brain Tissue Displacement and Strain is Elevated in Subjects with Chiari Malformation Type I Compared to Healthy Controls: A Study Using DENSE MRI - Blaise Simplice Talla Nwotchouang; Maggie S. Eppelheimer; Soroush Heidari Pahlavian; Jack W. Barrow; Daniel L. Barrow; Deqiang Qiu; Philip A. Allen; John N. Oshinski; Rouzbeh Amini; Francis Loth (Annals of Biomedical Engineering, 2021)

Novel, non-nitrocatechol catechol-O-methyltransferase inhibitors modulate dopamine neurotransmission in the frontal cortex and improve cognitive flexibility - Spencer Byers; Ingrid P. Buchler; Michael DePasquale; Helen L. Rowley; Rajiv S. Kulkarni; Lucy Pinder; Anna Kolobova; Cailian Li; Vinh Au; Daniel Akuma; Gongliang Zhang; Huijun Wei; et al. (Psychopharmacology, 2020)

Sex Differences in the Formation of Intracranial Aneurysms and Incidence and Outcome of Subarachnoid Hemorrhage: Review of Experimental and Human Studies - Nefize Turan; Robert Allen-James Heider; Dobromira Zaharieva; Faiz U. Ahmad; Daniel L. Barrow; Gustavo Pradilla (Translational Stroke Research, 2016)